Global Talent Flows - Kerr, Sari Pekkala; Kerr, William; Ozden, Caglar; Parsons, Christopher (World Bank, Washington, DC, 2016)
The global distribution of talent is highly skewed and the resources available to countries to develop and utilize their best and brightest vary substantially. The migration of skilled workers across countries tilts the deck even further. Using newly available data, the paper first reviews the landscape of global talent mobility, which is both asymmetric and rising in importance. Next, the determinants of global talent flows at the individual and firm levels are presented and some important implications are sketched. Third, the national gatekeepers for skilled migration and broad differences in approaches used to select migrants for admission are reviewed. Looking forward, the capacity of people, firms, and countries to successfully navigate this tangled web of global talent will be critical to their success.